The Existence of the Statement of the Companions (FatwÄ á¹¢aá¸¥Äba) and its á¸¤ujjah in Islamic Legal Thoughts - Pongoliu, Hamid (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2019)
FatwÄ á¹£ahÄba can be used as á¸¥ujjah (proof) even though the ulama (scholars) have different opinions regarding its validity. The ulama categorize the Companionsâ€™ fatwÄ as one of the sources of law decision which is still being disputed about the validity. It is different from the Qur'an, Sunnah, IjmÄâ€™, and QiyÄs that have been agreed by the most of the scholars as a source of Islamic law. The Companionsâ€™ fatwÄ has an influence on the development of Islamic law thought which can be substantially equated like a fiqh, because it is the result of istinbÄá¹ (efforts to extract the áº“annÄ« (speculative) sharia law from original sources through the mobilization of all natural reasoning abilities) and the results of the Companions ra'y (establish a law of contemporary problems that have not been found in the Qurâ€™an and hadith) which have been codified according to the particular mazhab. Therefore, the Companions fatwÄ is the result of the ijtihad of the Companions as ulama of the previous generation and became the á¸¥ujjah of the ulama until today who have colored Islamic law thought, such as fatwÄ of AbÅ« Bakr, Umar, â€˜UthmÄn, â€˜AlÄ«, â€˜AbdullÄh Ibn â€˜AbbÄs, â€˜AbdullÄh Ibn Mas'Å«d and other Companions. At least the fatwÄ á¹£aá¸¥aba can be used as á¸¥ujjah in istinbÄá¹ of islamic law when new problems arise, and no proposition is found in the Qur'an and hadith.